Eksklusi Spasial di Era Demokratisasi: Politik Ruang dan Zonasi Kawasan di Selayar - Slamet Riadi (ETNOSIA : Jurnal Etnografi Indonesia, 2019)
This research aims to know how the politics of space and developments area in Bontosunggu, has correlation with rural democratization’s discourse, especially in rural development planning. Some years ago, Bontosunggu had so many developments area program, such as building transportation infrastructure (Bandara) and rural economy development in west coastal area from this village. Some of this program namely KEK (Kawasan Ekonomi Khusus), PISEW (Pengembangan Infrastruktur Sosial-Ekonomi Wilayah). This study was conducted in Bontosunggu, Selayar in November 2018 until January 2019. Data was collected using in-depth interview, observation, and photograph interview. The participants in this research, consist of rural government, society in Kampung Bau, and policy government of Kabupaten Kepulauan Selayar (BAPPEDA and Dinas Pemerintahan Desa). The research finding indicates: Firstly, process of planning developments (KEK and PISEW) area in Bontosunggu has an impact on rural development orientations. Secondly, the politics of space in Bontosunggu has made a process of spatial exclusion to Kampung Bau. Thirdly, process of spatial exclusion to Kampung Bau, has correlated to the legitimation and regulation’s mechanism, then also with the development area and rural democratization’s process.